Green Human Resource Management dan Kinerja Lingkungan: Studi Kasus pada Rumah Sakit di Kota Palembang - Muhammad Ichsan Hadjri; Badia Perizade; Zunaidah Zunaidah; Wita Farla WK (Politeknik Negeri Bengkalis, 2020)
Based on the Environmental Quality Index reported by the Ministry of Environment and Forestry of the Republic of Indonesia, in 2017 the Environmental Quality Index rank of South Sumatra slipped to rank 20 nationally, wherein the previous year was ranked 16. Environmental performance was one of the factors in Environmental Quality Index. Most of the previous research on environmental performance and GHRM was carried out in the manufacturing industry analysis units, while other industrial fields have not been studied much including hospitals. In fact, the hospital is one of the business sectors that is quite related to the environment. This study aims to analyze the effect of GHRM which consists of the variables Green Recruitment and Selection (GRS), Green Training (GTR), and Green Compensation (GCO) partially or jointly on the performance of the hospital environment in Palembang City. The Grand Theory which is used in this research is Ecocentrism Theory and Triple Bottom Line. The population in this study were hospital employees at government hospitals in Palembang, totalling 2,270 people. By using the Slovin formula and the stratified proportional random sampling method, the number of samples who became respondents in this study was 248 people. This research is processed by multiple linear regression analysis techniques. The results showed that GRS, GTR, and GCO partially had a significant effect on environmental performance in hospitals in Palembang City. The results also show that GRS, GTR, and GCO together also have a significant effect on environmental performance.